Lifestyle vis-a-vis Anorectal Disorders - Gopal Singh; Ajay Kumar Gupta (AYUSHDHARA, 2023)
Ayurveda is science of life that aims at maintaining normal health of an individual along with treatment of various disorders. Appropriate Aahara (dietary habits) and Vihara (lifestyle) plays a vital role in maintaining normal health and also in treatment of various disorders along with the use of medication. In today’s era with rapid economic development there is an increase in irregular and inappropriate dietary habits and lifestyle, which are major reason for increase in a sedentary lifestyle and disturbed digestion (due to Mandagni) leading to occurrence of Gudagata Rogas (anorectal disorders) like Bhagandara (Fistula-in-ano), Arsha (haemorrhoids), Parikartika (fissure-in-ano), Guda Kandu (pruritis ani) etc. There disorders reoccur after sometime even after surgical intervention due to inappropriate Aahara (dietary habits) and Vihara (daily routine) of patients, so it’s very important to educate patients regarding Aahara and Vihara. In this article an effort is made to highlight a disciplined protocol in view of ancient Acharyas regarding appropriate Aahara and Vihara for a disease-free society.